Differential Gene Expression in Erlotinib-Treated Fibroblasts. Issue 2 (March 2019) - Wickersham, Karen E.; Hodges, Theresa K.; Edelman, Martin J.; Song, Yang; Nan, Mintong; Dorsey, Susan G.
Abstract : Background: Therapies targeting the epidermal growth factor receptor (EGFR) result in a painful rash, the most common and debilitating toxicity among patients with non-small cell lung cancer (NSCLC) who take EGFR tyrosine kinase inhibitor (TKI) therapy; however, predicting the development and the severity of the rash is difficult. Objective: The aim of this study was to examine how erlotinib—an EGFR TKI that NSCLC patients take to stop or slow tumor growth—altered the transcriptome of dermal fibroblasts. Methods: Dermal fibroblasts (ATCC PCS-201-012) were seeded in cell culture flasks, grown under standard conditions, and transferred to cell culture dishes. Cells were treated once daily for 3 days with erlotinib 100 nM ( n = 5), erlotinib 1 μM ( n = 5), vehicle 1 μM (dimethyl sulfoxide) ( n = 5), or no treatment ( n = 5). Total RNA was extracted using a standard TRIzol method and hybridized using Affymetrix GeneChip Human Genome U133 Plus 2.0 arrays. Raw intensities generated from the arrays were normalized using a Robust Multiarray Average method and analyzed using analysis of variance in Limma R software. Differentially expressed genes were analyzed using Ingenuity Pathway Analysis to identify canonical or noncanonical signaling pathways enriched in this dataset. Results: We selected genes for investigation based on their potential role in wound healing ( AQP3 ), rash development ( CCL2 ), fibroblast activation ( PALLD ), cancer and cancer progression ( GDF-15, SLC7A11, MMP12, and DIRAS3 ), and cell cycle control ( CDC6 ). We were able to validate four of these genes by both Western blot analysis and quantitative polymerase chain reaction ( MMP12, CCL2, CDC6, and SLC7A11 ). Discussion: If found predictive of rash in future studies using patient samples, our findings may help to identify those at risk for severe rash so that (a) the dose of EGFR TKI therapy may be adjusted; (b) additional treatments for the rash can be developed; and/or (c) precise, patient-centered interventions can be developed so that patients with cancer can better self-manage their rash and adhere to EGFR TKI treatment. Abstract : Supplemental digital content is available in the text.